A Review of Momentum as an Investment Strategy - Ranajee; Pathak, Rajesh; Kumar, Satish (Indian Journal of Finance, 2015)
Existing literature claims momentum as a profitable investment strategy. It is widely documented in finance literature that momentum profit has explanatory power, and it provides additional information for explaining the abnormal returns of the stocks. The paper was written with a purpose to report the findings of existing literature to identify decompose and define the dynamics of momentum as an investment strategy. The contribution of the study would broadly be four folded: (a) The outcome of the study fills the void in the existing stocks of literature on momentum investing strategies, (b) the presence of momentum profits may induce the investors to develop momentum investment strategies so as to minimize the vulnerability, and (c) understanding of the drivers of momentum profits in the up market and down market states of the market may help the market participants to devise their trading strategies under momentum investing, (d) the knowledge of volatility behaviour of winners, losers, and momentum profits and the volatility drivers of momentum would contribute to market participants in trading of volatility risk and returns.